Pests Control and Acarology - Haouas, Dalila; Hufnagel, Levente (IntechOpen, 2020)
Pests Control and Acarology presents novel methods adopted in pest management for cereal crops and fruit trees. Each chapter was written by experts in their respective areas, and provides a rigorous review and outline of current trends and future needs, to expedite progress in the field. The book was structured in three sections as follows. The first section introduces the topics and defines concepts of Integrated Pest Management and Biological Control. The second section includes two chapters: the first one discusses a new trap barrier system for rodent pest control in rice and the second one presents methods used in the management of stem borers in cereal crops. The third section presents various topics within the area of Acarology.